2016
DOI: 10.1371/journal.pone.0147552
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Changes and Fibrous Tissue Growth after Cochlear Implantation Are Correlated and Can Be Reduced Using a Dexamethasone Eluting Electrode

Abstract: BackgroundThe efficiency of cochlear implants (CIs) is affected by postoperative connective tissue growth around the electrode array. This tissue formation is thought to be the cause behind post-operative increases in impedance. Dexamethasone (DEX) eluting CIs may reduce fibrous tissue growth around the electrode array subsequently moderating elevations in impedance of the electrode contacts.MethodsFor this study, DEX was incorporated into the silicone of the CI electrode arrays at 1% and 10% (w/w) concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(176 citation statements)
references
References 43 publications
(55 reference statements)
8
154
5
1
Order By: Relevance
“…Thus, the results of the study might not indicate the impact of the RW and cochleostomy approaches on electrode impedance. Some studies showed that increased impedance had a correlation with fibrous tissue growth around the electrode [28,29]. In this study, there was no significant difference in the impedance between the RW and cochleostomy groups using the same electrode type at 4 time points, which may indicate that different surgical techniques might have similar degrees of fibrous growth.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Thus, the results of the study might not indicate the impact of the RW and cochleostomy approaches on electrode impedance. Some studies showed that increased impedance had a correlation with fibrous tissue growth around the electrode [28,29]. In this study, there was no significant difference in the impedance between the RW and cochleostomy groups using the same electrode type at 4 time points, which may indicate that different surgical techniques might have similar degrees of fibrous growth.…”
Section: Discussionmentioning
confidence: 45%
“…The minimal access CI group used dexamethasone before they inserted the electrode. However, some studies had shown that dexamethasone can significantly reduce tissue fibrosis, which would reduce electrode impedance [28]. Thus, the results of the study might not indicate the impact of the RW and cochleostomy approaches on electrode impedance.…”
Section: Discussionmentioning
confidence: 83%
“…Fibrous tissue growth, which was an underlying etiology we suspected might influence electrode impedance, is often more extensive in the base of the cochlea compared to more apical regions (e.g. Wilk et al 2016). To the extent that measured electrode impedance reflects the extent of tissue growth, impedance measures of electrodes located in the base might be more informative than more apically located electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Electrode impedance provides information about the status of the electrode and the surrounding environment, and has been shown to be sensitive to changes in tissue growth around the electrode array (Wilk et al 2016). Histological analysis of a temporal bone from a deceased CI recipient who experienced a complete loss of acoustic hearing in the implanted ear between one and four months after implantation revealed that although post mortem hair cell and neural counts were not significantly different for implanted and unimplanted ears, the implanted ear presented with extensive fibrous tissue in the cochlear scalae.…”
Section: Introductionmentioning
confidence: 99%
“…There are changes which occur over time and this further complicates the relationship. Significant impedance changes occur postoperatively for implanted electrodes [49] and this has motivated the development of steroid-eluting leads to prevent this [50].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%